Improving the vacuum-infusion process to manufacture high quality structural composite for the aeronautic market - Oliveira, Luís (2014)
In last years, the vacuum-infusion processing method is being replacing successfully autoclave technologies to manufacture advanced composite structures, namely, the carbon-fibre reinforced plastic (CFRP) ones, for aeronautical and aerospace applications. The high investment associated with autoclave “prepreg” manufacturing has prompted interest in the use of alternative vacuum-infusion technologies that proven to be much more cost-effective processing methods. The present work presents, describes and discusses improvements and developments made on an existing vacuum-infusion process to obtained high quality and reliable CRFP structural components to the aircraft industry. The first aim is to use the developed technology to produce wing elevators for an unmanned aerial vehicle (UAV), commonly known as “drone”, expected to be used in firefighting and policing civilian operations. An additional heating stage was enhanced to the initial standard vacuum process to increase the quality and reliability of the final manufactured composite parts, namely in terms of void reduction and control of fibre content and orientation. A prototype part was manufactured by using this improved vacuum-infusion process to be tested and validate the developed technology. This paper will present and discuss the results obtained in the manufacturing and characterization tests made on the produced prototypes.